2016
DOI: 10.1021/acs.langmuir.6b00978
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Phospholipids and Organic Phases: Insights into Lipoproteins and Nanoemulsions

Abstract: The adsorption of phosphatidylcholines (PCs), dissolved in squalene or squalane as an organic phase, was studied at the interface with water. Using profile analysis tensiometry, the equilibrium adsorption isotherms, minimum molecular interfacial areas, and solubility limits were derived. For squalene, differences in PC solubility and interfacial adsorption were found, depending on PC saturation. Compared to saturated PCs, unsaturated PCs showed a 3-fold-lower interfacial density but up to a 28-fold-higher crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…Interfacial tensions are commonly measured with optical methods. Profile analysis tensiometry (PAT) has been used extensively to determine the adsorption process of surfactants [20][21][22] and is considered as non-invasive. The Du Noüy ring is one of the first established methods that allowed interfacial measurements [23].…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial tensions are commonly measured with optical methods. Profile analysis tensiometry (PAT) has been used extensively to determine the adsorption process of surfactants [20][21][22] and is considered as non-invasive. The Du Noüy ring is one of the first established methods that allowed interfacial measurements [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of DPPC/DSPE-PEG 2000 , we found that it takes approximately two hours to obtain a visible white thin layer ( Figure 2). However, we might also speculate that this 'thin layer' can be composed of multiple layers mainly composed of DPPC, as demonstrated by tensiometric measurements at oil-water interfaces by Hildebrandt et al [25,30].…”
Section: Resultsmentioning
confidence: 90%
“…Nano-emulsions (150 mL) were freshly prepared from a PL solution in squalene (typically 1 mg PL/mL squalene) [25,26]. In optimisation studies, we used different water fractions (1, 3, 5 and 10% w/o v/v) for a fixed lipid composition (DPPC/DOTAP (1:1 mol:mol).…”
Section: Preparation Of W/o Nanoemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of squalene as dispersion medium, moving the probing group down along the acyl chains, S immediately decreases but then tends to stabilize, maintaining in the case of 14-PCSL a higher value than observed using dodecane as the oil. This is most likely caused by the insertion of the bulky and sterically hindered squalene molecules among the lipid tail termini, which leads to a decrease in the chain termini mobility [ 41 ]. However, because of its molecular structure, squalene is not able to be enter into the monolayer interior.…”
Section: Resultsmentioning
confidence: 99%